2009
DOI: 10.1007/s11120-009-9434-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen detection in biological systems

Abstract: This article presents a brief description of analytical tools for monitoring evolution and consumption of molecular dioxygen in biological organisms. Based on its nature as a gas and its physical and chemical properties of the ground state ³Σ(g)O₂; different approaches have been developed for quantitative determinations: (i) manometry, (ii) formation of titratable sediments, (iii) solid state electrodes, (iv) EPR oximetry, (v) luminescence quenching, (vi) biological sensoring, (vii) mass spectrometry and (viii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Therefore, data concerning catalytic rates and turnover numbers (stability) of newly synthetized O 2 -evolving catalysts are highly important for their further development. In this regard, in addition to traditionally used amperometric methods for O 2 detection (Renger and Hanssum, 2009), TR-MIMS can be applied as a highly sensitive method for studying the O 2 -evolving capability of these complexes. However, a major advantage and uniqueness of the TR-MIMS technique in this field is that, in combination with 18 O-labeling experiments, it can be employed for studying the pathways of O 2 formation in reactions catalyzed by the ‘potential’ solar water-oxidation catalysts (Poulsen et al, 2005; Beckmann et al, 2008; Sala et al, 2010; Shevela et al, 2011b; Najafpour et al, 2012; Vigara et al, 2012).…”
Section: Applications In Artificial Photosynthesismentioning
confidence: 99%
“…Therefore, data concerning catalytic rates and turnover numbers (stability) of newly synthetized O 2 -evolving catalysts are highly important for their further development. In this regard, in addition to traditionally used amperometric methods for O 2 detection (Renger and Hanssum, 2009), TR-MIMS can be applied as a highly sensitive method for studying the O 2 -evolving capability of these complexes. However, a major advantage and uniqueness of the TR-MIMS technique in this field is that, in combination with 18 O-labeling experiments, it can be employed for studying the pathways of O 2 formation in reactions catalyzed by the ‘potential’ solar water-oxidation catalysts (Poulsen et al, 2005; Beckmann et al, 2008; Sala et al, 2010; Shevela et al, 2011b; Najafpour et al, 2012; Vigara et al, 2012).…”
Section: Applications In Artificial Photosynthesismentioning
confidence: 99%
“…Amperometric technique is currently by far the most frequently used approach for studies of oxygen evolution from sample suspensions (rev Renger and Hanssum 2009). In this study, we used the solid state Zr oxide electrode, used before in a few cases (Björkman and Gauhl 1970; Greenbaum and Mauzerall 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Renger and Hanssum 2009). In order to obtain the maximally fast (ms) response, a thin layer of cells was placed directly on the bare platinum electrode (Joliot 1967), but this sacrificed the absolute calibration of the response (Renger and Hanssum 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offering large accessibility to atomic and molecular species of the ambient atmosphere, the microscopic structure of these sites at the surface is also influenced by the environment [7]. Molecular oxygen, O 2 , plays a crucial role since it is active in several reactions and it can diffuse through the nanostructured silica [8,9]. Previous studies have demonstrated the formation of oxygen related defects by controlled thermochemical reactions.…”
Section: Introductionmentioning
confidence: 99%